Desenvolvimento da escala de conhecimento sobre abuso sexual infantil - Lazarini, Denise Elizandra (2013)
To assess the children's knowledge about the subject Child sexual abuse is a form of prevention. Information about sexual abuse should be increasingly propagated in society in order to strengthen the repertoire of self-protection child. This study aimed to develop the Scale Knowledge about Sexual Abuse - teenage version from the Questionnaire on Factors Related to Sexual Abuse (Padilha, 2007) for a population of 9 to 14 years in the city of Curitiba and its metropolitan area. For that studies have been performed with three samples containing 23 participants in total, between 08 and 12 years of age, in elementary school, of both sexes, housed in institutions assisted by the Foundation for Social Welfare and attended by CREAS São José dos Pinhais. The original items needed to undergo changes, moreover, was indispensable to the creation of new items and adaptation via semantic analysis. The final scale was easily understood by the participants that the items discriminated clearly developed.